HF progression among outpatients with HF in a community setting. (15th February 2019) - Iorio, Annamaria; Rea, Federico; Barbati, Giulia; Scagnetto, Arjuna; Peruzzi, Elena; Garavaglia, Agnese; Corrao, Giovanni; Sinagra, Gianfranco; Di Lenarda, Andrea
Abstract: Background: Incidence and prognostic impact of heart failure (HF) progression has been not well addressed. Methods: From 2009 until 2015, consecutive ambulatory HF patients were recruited. HF progression was defined by the presence of at least two of the following criteria: step up of ≥1 New York Heart Association (NYHA) class; decrease LVEF ≥ 10 points; association of diuretics or increase ≥ 50% of furosemide dosage, or HF hospitalization. Results: 2528 met study criteria (mean age 76; 42% women). Of these, 48% had ischemic heart disease, 18% patients with LVEF ≤ 35%. During a median follow-up of 2.4 years, overall mortality was 31% (95% CI: 29%–33%), whereas rate of HF progression or death was 57% (95% CI: 55%–59%). The 4-year incidence of HF progression was 39% (95% CI: 37%–41%) whereas the competing mortality rate was 18% (95% CI: 16%–19%). Rates of HF progression and death were higher in HF patients with LVEF ≤ 35% vs >35% (HF progression: 42% vs 38%, p  = 0.012; death as a competing risk: 22% vs 17%, p  = 0.002). HF progression identified HF patients with a worse survival (HR = 3.16, 95% CI: 2.75–3.72). In cause-specific Cox models, age, previous HF hospitalization, chronic obstructive pulmonary disease, chronic kidney disease, anemia, sex, LVEF ≤ 35% emerged as prognostic factors of HF progression. Conclusions: Among outpatients with HF, at 4 years 39% presented a HF progression, while 18% died before any sign of HF progression. This trend was higher in patients with LVEF ≤ 35%. These findings may have implications for healthcare planning and resource allocation. Highlights: HF remains a condition with high morbidity and mortality rates. HF progression was higher in patients with LVEF ≤ 35% than patients with LVEF > 35%. Patients developing HF progression during the follow-up had a worse survival rate.